Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Qin, Wang-Jun; Noori, Hamid Reza (Psychopharmacology, 2016)
Rationale: Drug-induced sensitization in the mesocorticolimbic systems is thought to play an important role in certain aspects of drug addiction, including the involvement of drug-associated cues and environments in mediating drug-seeking behaviors. Our previous studies have identified the significance of heat shock protein 70 (Hsp70) in the development of a single morphine exposure-induced behavioral sensitization. Objectives: The present study expands upon these findings by investigating the effect of environment on the expression of behavioral sensitization induced by a single morphine exposure, and the potential involvement of Hsp70 protein levels in these effects. Methods: Mice were pretreated with a single morphine injection in test chambers (morphine-paired) or home cages (morphine-unpaired) on day 1 and challenged on day 2 or 8, in test chambers. Hsp70 expression in the nucleus accumbens (NAc) was analyzed after the challenge. Results: The expression of single morphine exposure-induced behavioral sensitization was accompanied by a significant increase in Hsp70 expression in NAc. In contrast, the unpaired morphine-treated group failed to exhibit behavioral sensitization or higher Hsp70 expression. Additionally, by adding a habituation process prior to the challenge, we demonstrated that conditioned hyperactivity, which was not accompanied by an increased expression of Hsp70, is not essential for behavioral sensitization. Conclusions: Behavioral sensitization induced by a single morphine exposure in mice exhibits context and time dependency, with environmental context likely functioning via an inhibitory conditioning mechanism. Furthermore, alterations in Hsp70 expression in the NAc may represent a neurobiological sensitization mechanism mediating context- and time-dependent behavioral sensitization.
Gesehen am 13.06.2019